Septorhinoplasty and the Late Impact on Olfactory Function: A Review and Meta-analysis - Sousa, Francisco Alves de; Santos, Mariline; Correia, João Tavares; Pinto, Ana Nóbrega; Meireles, Luís; Ferreira, Miguel (Facial Plastic Surgery, 2023)
Septorhinoplasty (SRP) is one of the most commonly performed procedures worldwide. There is a recognized debate about the impact of nasal surgery on olfactory function (OF). The study's objective was to assess the effect of SRP on late postoperative OF. A comprehensive review and meta-analysis were employed to assess OF after SRP. All the integrated studies used objective instruments to quantify OF before and after surgery. A literature search was conducted, and the selected works were evaluated, computed, and finally included in a meta-analysis. The risk of bias was assessed using the NIH Guidance for Evaluating the Quality of Before-After (Pre-Post) Studies with No Control Group. Only the latest follow-up OF measurements provided by each research were considered in the analysis. The 95% confidence interval of the effect magnitude for each study was calculated to elucidate effect sizes. Eleven studies were included in the analysis. Five studies reported late OF improvement (45.5%), five reported no alteration in OF (45.5%), and only one study reported OF impairment after SRP (9%). Some works described a transitory decline in OF shortly following surgery, followed by postoperative improvement. A pooled meta-analysis showed that OF was not significantly altered after SRP (p = 0.10) in the late follow-up. SRP surgery seems to constitute a safe procedure concerning OF in the long term. According to research, OF may deteriorate temporarily after surgery with later improvement, sometimes to higher values than baseline. The anticipated evolution of OF after intervention could be discussed during the preoperative consultation for SRP.
Keywords: septorhinoplasty; olfaction; smell; nose; surgery